2014
DOI: 10.1002/bit.25477
|View full text |Cite
|
Sign up to set email alerts
|

Separation of in‐vitro‐derived megakaryocytes and platelets using spinning‐membrane filtration

Abstract: In-vitro-derived platelets (PLTs) could potentially overcome problems associated with donated PLTs, including contamination and alloimmunization. Although several groups have produced functional PLTs from stem cells in vitro, the challenge of developing this technology to yield transfusable PLT units has yet to be addressed. The asynchronous nature of in vitro PLT generation makes a single harvest point infeasible for collecting PLTs as soon as they are formed. The current standard of performing manual centrif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 45 publications
(54 reference statements)
0
23
0
Order By: Relevance
“…To determine if ULA-like culture would affect primary human MK maturation and PPF, mPB CD34 + HSPCs from 2 different donors were first differentiated to MKs on a TC surface, as previously described [37]. On day 7, the culture was selected for CD41 + MKs, which were then reseeded on either a TC or polyHEMA-coated surface in the presence of Nic.…”
Section: Resultsmentioning
confidence: 99%
“…To determine if ULA-like culture would affect primary human MK maturation and PPF, mPB CD34 + HSPCs from 2 different donors were first differentiated to MKs on a TC surface, as previously described [37]. On day 7, the culture was selected for CD41 + MKs, which were then reseeded on either a TC or polyHEMA-coated surface in the presence of Nic.…”
Section: Resultsmentioning
confidence: 99%
“…Different 3D tools have been described thus far in the attempt of supporting thrombopoiesis by both mouse and human Mks differentiated from either hematopoietic progenitors or the promising induced pluripotent stem cells. 4,5,[55][56][57][58][59] Despite the usefulness for the advancement in providing systems for platelet production, all these models did not reproduce the complex microenvironment where megakaryopoiesis physiologically takes place. In this regard, a fundamental advantage of our model is its ability to provide the first ex vivo tissue system able to reproduce the 3D structure of the bone marrow niche, in combination with ECM components and physiologic shear rate, for the study of Mk function and platelet formation.…”
Section: Discussionmentioning
confidence: 99%
“…21,[38][39][40] The effects of modulating and/or inhibiting this pathway to increase megakaryocyte numbers should be further explored to optimize maturation of undamaged megakaryocyte populations. One study showed that the overexpression of Bcl-xL in human megakaryocytes increased proliferative capacity and survival.…”
Section: Overcoming the Challenges Megakaryocyte In Vitro Injuriesmentioning
confidence: 99%